Hybrid Polymer Capacitor
Patent Information
- Application Number
- JP2024550182
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-25
- Filing Date
- 2023-02-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-02-23
Smart Images

Figure 2025505857000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a hybrid polymer capacitor. [Background technology]
[0002] Hybrid polymer capacitors are used in electronic circuits where high capacitance and voltage range, low ESR, enhanced ripple current capability, or wide operating temperature range are required in a compact design. Capacitor manufacturers can provide hybrid polymer capacitors with a low voltage range. For example, US Pat. No. 5,299,433 or US Pat. No. 5,399,433 disclose state-of-the-art hybrid polymer capacitors. The capacitors are limited to low operating voltages. The maximum breakdown voltage disclosed amounts to 119V.
[0003] Hybrid polymer capacitors are susceptible to short circuits (breakdown) between the anode and cathode electrodes when operating voltages above 150 V are used, therefore other capacitor types such as film capacitors are used in electronic circuits with operating voltages higher than 150 V.
[0004] Until now, capacitor manufacturers have not been able to develop and produce high voltage hybrid polymer capacitors because they were not reliable enough for use in commercial electronic circuits, but for example, capacitor voltage classes of 400V and above are becoming relevant for electric vehicle chargers and inverters. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] US Patent No. 8,462,484 B2 [Patent Document 2] U.S. Patent No. 9,959,981 B2 Summary of the Invention
[0006] The present invention provides an improved hybrid polymer capacitor that includes several layers disposed between an anode layer and a cathode layer.
[0007] The anode layer forms the anode electrode of the capacitor, and the cathode layer forms the cathode electrode of the capacitor.
[0008] Further, a non-hydrated metal oxide layer is provided, which is also referred to below as oxide layer, and has a thickness of at least 100 nm in the stacking direction. In this specification, the stacking direction is the direction in which the anode layer and the cathode layer face each other and the several layers are stacked. The stacking direction is therefore also the direction of the electric field applied to the capacitor and the direction of the current in case of capacitor breakdown.
[0009] Herein, the oxide layer serves as an electrical insulating layer between the anode and the cathode.
[0010] In preferred embodiments, the thickness of the non-hydrated metal oxide layer may be greater than 110 nm, or greater than 120 nm.
[0011] In a preferred embodiment, the anode comprises an anode foil comprising one or more anode layers, and the cathode comprises a cathode foil comprising one or more cathode layers. Either the anode or the cathode may comprise a metal, preferably aluminium. Aluminium has favourable electrochemical properties suitable for application in capacitors.
[0012] The anode and cathode layers may furthermore be provided with a porous structure with an advantageously large surface. Pores may be actively etched in the anode or cathode material. In particular, the surface of the cathode layer may comprise a roughened, spongy or grape-like structure to enhance the surface area.
[0013] The capacitor further comprises a liquid electrolyte having a conductivity of at least 200 μS / cm measured at 30° C. and a water content of at least 0.5% (for electrolyte, percentage is defined as w / w % (weight of water / total weight of electrolyte)). The conductivity of the liquid electrolyte may be significantly higher than 200 μS / cm. In particular, the conductivity may amount to 2500 μS / cm at 30° C. The surface of the oxide layer is impregnated with the liquid electrolyte.
[0014] A minimum thickness of the electrically insulating oxide layer is essential to provide a certain breakdown voltage of the capacitor. The breakdown voltage is determined experimentally as follows: To determine the breakdown voltage, the capacitor is provided with a series resistance of 1000 Ω and subjected to a voltage increase starting from 0 V with a voltage step of 1 V / s. The resulting current is measured. The voltage value at which the resulting current exceeds 500 μA is identified as the breakdown voltage.
[0015] The oxide layer may contain separate voids with diameters in the nanometer range. Such voids may be densely distributed throughout the oxide layer. Increasing the thickness of the oxide layer may result in a greater number of voids. Also, the density of the voids may increase. During operation, the separate voids may condense into larger void structures and may reach the surface of the oxide layer.
[0016] Thus, conductive materials such as polymer nanoparticles that may be provided on the surface of the oxide layer may penetrate the voids and form conductive paths through the oxide layer, thereby causing a reduction in the breakdown voltage of the capacitor.
[0017] A specific liquid electrolyte with a conductivity of at least 200 μS / cm measured at 30° C. and a water content of at least 0.5% is suitable for improving the oxide layer during the operation of the capacitor by its oxidizing ability, thus at least suppressing or even avoiding the formation of unwanted void structures that may impair the electrical insulating properties of the oxide layer and reduce the breakdown voltage.
[0018] The liquid electrolyte is impregnated into the surface of the capacitor layers, particularly the oxide layer. The electrolyte has the ability to oxidize the anode metal to improve the oxide layer, and to avoid or close unwanted void structures in the oxide layer. The water content of the electrolyte is preferably 0.5% to 7% or 0.5% to 5%, more preferably 0.5% to 3%. The effective reoxidation is improved by optimizing the water content of the liquid electrolyte as described above.
[0019] Thus, the capacitor can withstand voltages in excess of 150V, preferably in excess of 250V, and more preferably at least 400V or up to 450V.
[0020] Furthermore, the sparkover voltage at which the liquid electrolyte begins to form a thicker oxide layer is preferably greater than 400V at 85°C.
[0021] Sparkover voltage is a characteristic of the electrolyte measured in a beaker over an electrolyte without a separator layer and only with a defined distance between the anode and cathode foils. The breakdown voltage is higher than the sparkover voltage because the separator layer of the capacitor limits the total amount of electrolyte and limits the movement of ions in the electrolyte.
[0022] Hybrid polymer capacitors are cheaper than film capacitors due to the smaller size of the components for the same capacitance, and also due to their superior heat dissipation capabilities leading to more economical and compact heat sink and cooling unit designs. The hybrid polymer capacitor according to the present invention can replace film capacitors at operating voltages above 150V.
[0023] Furthermore, hybrid polymer capacitors can have increased reliability due to their described self-healing properties.
[0024] In a preferred embodiment, the anode layer comprises aluminum and the oxide layer comprises aluminum oxide Al2O3, also called alumina. Preferably, the layers consist of these materials.
[0025] Aluminum has favorable electrochemical properties. Furthermore, alumina is a well-known good electrical insulator, making it suitable for application in capacitors.
[0026] In one embodiment, the oxide layer is applied directly to the surface of the anode layer.
[0027] In the stacking direction, the oxide layer and the anode layer are adjacent to each other. The oxide layer may comprise an oxidized anode material. In particular, the oxide layer may be formed in the manufacturing process by oxidizing the anode layer with a strong forming electrolyte, such as an aqueous dicarboxylic acid or borate type solution, different from the liquid electrolyte used during operation of the capacitor.
[0028] Further, some layers of the capacitor include a hydrated metal oxide layer disposed on a surface of a non-hydrated metal oxide layer, the non-hydrated metal oxide layer being disposed on a surface of the oxide layer opposite the anode in the stacking direction, and the hydrated metal oxide layer may have a thickness of at least 10 nm in the stacking direction.
[0029] The hydrated oxide layer serves as a protective layer for the non-hydrated oxide layer, which is formed by applying an aqueous solution of an oxidizing electrolyte during the manufacturing process. The hydrated oxide layer can be formed by a specific hydration process, e.g. boiling, using appropriate forming salts as a pretreatment and a special temperature profile treatment during the annealing step of the anode foil.
[0030] In particular, the hydrated oxide layer at least partially prevents the penetration of the conductive polymer nanoparticles into the bulk of the oxide layer, thus preventing sparking and increasing the breakdown voltage. In combination with the oxidizing ability of the liquid electrolyte, the hydrated oxide layer therefore prevents electrical shorts through the oxide layer.
[0031] The hydrated oxide layer is less dense but more homogeneous than the non-hydrated oxide layer, therefore the preferred thickness of the hydrated oxide layer is at least 10 nm.
[0032] In particular, the hydrated oxide layer may comprise hydrated alumina, which is hydrated Al2O3, ie, Al2O3·xH2O, where x is from 0.1 to 3.0, inclusive.
[0033] In one embodiment, the non-hydrated oxide layer, the hydrated oxide layer, or both oxide layers are doped with phosphorus. To this end, for example, phosphate anions PO4 3- is added to the oxide layer forming solution. The minimum atomic percentage of phosphorus in the oxide layer is preferably at least 0.01%. Anions are added to stabilize the layer structure, avoiding the creation of unwanted void structures, thus improving the breakdown characteristics of the capacitor.
[0034] In one embodiment, the non-hydrated oxide layer, preferably an alumina layer, comprises a stack of an amorphous oxide layer and a crystalline oxide layer, in particular an amorphous alumina layer and a crystalline alumina layer.
[0035] In a preferred embodiment, the oxide layer comprises an amorphous Al2O3 layer and a crystalline γ-Al2O3 layer, with a layer thickness ratio of the thickness of the crystalline layer / thickness of the amorphous layer being >0.1. The amorphous layer may be applied directly to the surface of the anode layer. The crystalline layer may be applied directly to the opposite surface of the amorphous layer. The amorphous layer has fewer structural defects than the crystalline layer and therefore better sealing properties, but the crystalline layer can be applied to a greater thickness, so that the breakdown voltage of the capacitor can be increased by the combination of both layers.
[0036] In one embodiment, the capacitor has a voltage rating greater than 150V, preferably greater than 250V. More preferably, the capacitor has a voltage rating of at least 400V or 450V.
[0037] Thus, the present invention allows for the use of hybrid polymer capacitors with extended voltage ratings, greater than 150 V. Compared to other capacitor types, hybrid polymer capacitors also allow for superior capacitance / volume ratios, low ESR (equivalent series resistance) at high frequencies, and low ESR at low temperatures.
[0038] The requirement of miniaturization and cost reduction can be achieved by using hybrid polymer capacitors, because the size of the components is small and their excellent heat dissipation capability allows the design of heat sinks and cooling units to be more economical and more compact, so for the same capacitance, hybrid polymer capacitors are smaller and cheaper than, for example, film capacitors.
[0039] In one embodiment, a polymer layer comprising a conductive polymer is disposed between one or more oxide layers, a non-hydrated oxide layer and an optional hydrated oxide layer, on one side and a cathode layer on the opposite side.
[0040] The polymer effectively functions as the cathode layer of the capacitor.
[0041] The polymer is preferably applied by impregnating the capacitor layer with a dispersion of the conductive polymer, whereby nanoparticles of the conductive polymer are applied to the outer surface of the oxide layer that does not face the anode or another oxide layer. The applied nanoparticles aggregate to form the polymer layer.
[0042] Additionally, the polymeric nanoparticles can permeate the hydrated and non-hydrated oxide layers, as well as other adjacent layers, such as the separator layer or cathode layer, thereby enhancing the electrical conductivity of these layers.
[0043] The polymer layer preferably comprises a PEDOT:PSS polymer material, which means poly(3,4-ethylenedioxythiophene) polystyrenesulfonate, a polymeric mixture of two ionomers (PEDOT and PSS), which exhibits favorable properties for use as a conductive polymer in a capacitor.
[0044] The properties of the hybrid polymer material PEDOT:PSS result in a favorably low ESR level for the capacitor, even at low temperatures.
[0045] Preferably, a separator layer having a separator withstand factor of at least 5% is disposed between the polymer layer and the cathode layer, and more preferably, the resistivity is at least 15%.
[0046] The separator layer is sandwiched between the anode and cathode layers to prevent direct contact between the electrodes.
[0047] The breakdown phenomenon of a capacitor depends on the characteristics of the insulating oxide layer and the separator as well as on the rated voltage of the capacitor.
[0048] The characteristics of the separator layer are at least its material type, density, and thickness, which are more specifically determined by the separator resistivity, which in turn determines the breakdown voltage.
[0049] The separator can be impregnated with a liquid electrolyte to fill all of the pores in the separator that were not reached by the polymer nanoparticles during polymer impregnation.
[0050] Furthermore, after impregnation, the electrolyte fills the pores in the anode and cathode foils, thus maximizing the capacitance of the capacitor since no or minimal voids remain in the electrodes.
[0051] In one embodiment, the separator layer has a minimum thickness of 50 μm.
[0052] In one embodiment, the separator layer has a density of at least 0.30 g / cm 3 It is.
[0053] Both of the above-mentioned characteristics of the separator layer increase the resistivity of the separator layer and therefore the breakdown voltage of the capacitor.
[0054] Resistivity is defined herein as the basis weight of the separator / voltage rating of the capacitor.
[0055] The basis weight of the separator is g / m 2 The unit is defined as the density of the separator times its thickness.
[0056] In one embodiment, the separator layer comprises natural and / or artificial fibrous material arranged in a single layer or multiple layers. Preferably, the average mass / area ratio of the separator layer is less than 8.0 g / m 2 Greater than.
[0057] In one embodiment, the separator layer includes a filter membrane layer, and the filter membrane material may include PET, nylon, PTFE (polytetrafluoroethylene) and / or PES (polyethersulfone). The filter membrane may include pores with a pore size greater than 0.22 μm. If the pore size is too large and the membrane becomes fragile, the separator may include an additional support layer.
[0058] The pores allow for impregnation of the separator layer with the conductive polymer and liquid electrolyte.
[0059] In one embodiment, an intermediate electrolyte layer is disposed between the polymer layer and the separator layer. The intermediate electrolyte layer may be provided to increase the breakdown voltage.
[0060] The intermediate electrolyte layer includes an intermediate electrolyte. The intermediate electrolyte may be a conductive viscous material disposed between the polymer layer and the separator layer. The intermediate electrolyte may be in contact with the polymer layer. The intermediate electrolyte may be in contact with the separator layer. The intermediate electrolyte may differ from the liquid electrolytes described above in terms of its composition.
[0061] The intermediate electrolyte can prevent the liquid electrolyte from contacting the polymer layer excessively, thereby preventing the liquid electrolyte from damaging, degrading, or expanding the polymer layer. Because the intermediate electrolyte is disposed between the liquid electrolyte and the polymer layer, more aggressive materials with better oxidizing ability can be used in the liquid electrolyte. Thus, the use of the intermediate electrolyte can enable the use of materials for the liquid electrolyte other than GBL (gamma-butyrolactone) and sulfolane solvent. Thus, it allows the construction of capacitors that can withstand higher voltages.
[0062] The liquid electrolyte may also be a conductive viscous material. A voltage may be applied to the liquid electrolyte through the cathode foil. The liquid electrolyte may act as the second electrode of the capacitor.
[0063] The liquid electrolyte and the intermediate electrolyte may have different compositions. For example, the liquid electrolyte may contain ethylene glycol, and the intermediate electrolyte may not contain ethylene glycol. In this case, the intermediate electrolyte without ethylene glycol can ensure that the polymer is not damaged by ethylene glycol. At the same time, the liquid electrolyte with ethylene glycol can ensure that the advantageous properties of ethylene glycol can be utilized.
[0064] The intermediate electrolyte may include a polyol and a conductive salt, which can ensure that the intermediate electrolyte is conductive.
[0065] In further embodiments, one or more of a carbon layer, a titanium layer, a titanium oxide layer, and a silicon dioxide layer are disposed between the cathode layer and the separator layer. In addition, the cathode foil can be oxidized. Thus, the cathode foil can have an artificially formed cathode oxide layer. The cathode oxide layer can be thicker than the natural oxide with a thickness of 2 nm to 3 nm. These layers protect the cathode metal material and provide additional resistance, thus allowing for further improvement of the breakdown voltage.
[0066] In one embodiment, the several layers between the anode layer and the cathode layer are stacked in the order described above.
[0067] In particular, some layers may be stacked in the following order. Optional layers may be omitted. The order of layers may be anode layer, (non-hydrated) oxide layer, hydrated oxide layer, polymer layer, intermediate electrolyte layer, separator layer, and cathode layer. The layers may abut adjacent layers in the above order. Again, optional layers may be omitted.
[0068] In different embodiments, the hybrid polymer capacitor may be either a flat-type or a wound-type capacitor. [Brief description of the drawings]
[0069] The present invention will now be described in more detail with reference to the accompanying drawings, in which: The present invention is not limited to the combination of features or elements shown in the drawings and embodiments.
[0070] Similar or apparently identical elements in the figures are marked with the same reference numbers. The proportions in the figures and illustrations are not to scale. [Figure 1] FIG. 1 is a schematic diagram of a first embodiment of a hybrid polymer capacitor according to the present invention. [Diagram 2] FIG. 1 is a partial cross-sectional TEM view of an anode foil having a coated layer. [Diagram 3] FIG. 1 shows an illustrative test film for measuring the resistivity of a polymer film. [Figure 4] FIG. 2 is a schematic diagram of a second embodiment of a hybrid polymer capacitor including a viscous electrolyte layer. [Diagram 5] FIG. 13 is a schematic diagram of a third embodiment of a hybrid polymer capacitor including a carbon layer. [Figure 6] FIG. 13 is a schematic diagram of a third embodiment of a hybrid polymer capacitor including a titanium layer and a silicon dioxide layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0071] FIG. 1 illustrates a first embodiment of a hybrid polymer capacitor 100 in accordance with the present invention.
[0072] The overall geometry of the capacitor 100 can be designed as a wound capacitor 100 or a flat capacitor 100. Different types of capacitor 100 housings of both geometries are possible.
[0073] The hybrid polymer capacitor 100 includes a stack of several layers.
[0074] The capacitor 100 is incorporated into an electrical circuit and includes at least two electrodes, an anode and a cathode, connected to tabs or terminals for external electrical contact. In particular, the anode and cathode electrodes are electrically connected to external positive and negative pins by using lead tabs. The capacitor may be integrated into an electrical circuit, for example, as an electrical filter or as a storage component.
[0075] The anode, in the embodiment shown, comprises a metallic anode foil 1. The foil comprises one anode layer 1, preferably made of aluminium.
[0076] The anode foil 1 in this example is porous in order to increase the surface of the layer.
[0077] An oxide layer 2 is applied to the surface of the anode foil 1. The oxide layer 2 comprises an oxidized anode metal material. In particular, the oxide layer 2 is applied by anodization of the anode metal material. In this embodiment, the oxide layer 2 comprises oxidized aluminum, in particular alumina (Al2O3).
[0078] The oxide layer 2 preferably has a thickness of 100 nm or more. This minimum thickness of the oxide layer 2 is necessary to provide the required minimum allowable breakdown voltage of the capacitor 100.
[0079] In this example, the oxide layer 2 comprises several layers. The oxide layer 2 comprises an amorphous Al2O3 layer 2a and a crystalline γ-Al2O3 layer 2b, with a layer thickness ratio of crystalline layer thickness / amorphous layer thickness >0.1. The amorphous layer 2a is applied directly to the surface of the anode foil 1. The crystalline layer 2b is applied directly to the opposite side of the amorphous layer 2a.
[0080] The two layers 2a and 2b are also shown in figure 2. Figure 2 represents a TEM (transmission electron microscopy) partial cross-section of an anode foil 1 coated with layers 2a and 2b.
[0081] The initial leakage current at the anode electrode is low and stable during the operation of the capacitor 100. However, the oxide layer 2 contains isolated voids with diameters in the nanometer range, which are densely distributed on the oxide layer 2. During operation, the isolated voids may condense into larger void structures, reach the surface of the oxide layer 2, and further interact with the conductive polymer nanoparticles on the surface of the oxide layer 2, causing a decrease in the breakdown voltage of the capacitor 100.
[0082] Therefore, the stability of the oxide layer can be increased by a series of chemical or thermal relaxation and modification processes during fabrication, which can further reduce the initial leakage current during operation of the capacitor 100.
[0083] On the surface of the oxide layer 2 opposite the anode foil 1 is applied a hydrous oxide layer 3. The hydrous oxide layer 3 comprises a hydrous oxidized anode metal material.
[0084] In this embodiment, the hydrous oxide layer 3 comprises hydrous alumina, which is hydrated Al2O3, ie, Al2O3·xH2O, where x is selected in the range of 0.1 to 3.0.
[0085] The preferred minimum thickness of oxide layer 2 is 10 nm. Oxide layer 2 and hydrous oxide layer 3 are formed during the manufacturing process of capacitor 100 by applying an aqueous solution of a strong oxide electrolyte.
[0086] The hydrated oxide layer 3 protects the oxide layer 2 as follows.
[0087] Firstly, the hydrous oxide layer 3 is an additional electrically insulating layer to increase the breakdown voltage.
[0088] Secondly, the oxide layer 2 contains natural cracks and voids on the surface of the layer, generated for example by mechanical or thermal stress. The hydrated oxide layer 3 is a less dense but more homogeneous layer, which prevents for example the conductive polymer nanoparticles from penetrating into the bulk of the oxide layer 2.
[0089] Thus, the hydrated oxide layer 3 prevents sparking in the oxide layer 2 due to its very high electrical conductivity.
[0090] Therefore, a sufficient thickness of more than 10 nm of hydrated oxide is required.
[0091] The oxide layer 2 and the hydrous oxide layer 3 are preferably doped with a phosphorus content of at least 0.01% atomic percentage to stabilize their structure and avoid void formation processes.
[0092] A polymer layer 4 is deposited on the surface of the hydrated oxide layer 3 opposite the oxide layer 2 and the anode foil 1. The polymer layer 4 is electrically conductive and contains a conductive polymer, preferably PEDOT:PSS, which stands for poly(3,4-ethylenedioxythiophene) polystyrenesulfonate, which is a polymeric mixture of two ionomers (PEDOT and PSS).
[0093] The polymer is applied by impregnation with a dispersion of the conductive polymer, which allows the conductive polymer nanoparticles to penetrate adjacent layers such as the separator layer 5 and the cathode foil 6 and increase the conductivity of these layers. On the other hand, the hydrated oxide layer 3 prevents the conductive polymer nanoparticles from penetrating into the non-hydrated oxide layer 2.
[0094] The polymer in the polymer layer 4 is homogeneously distributed to improve the electrical performance of the capacitor 100, such as capacitance, ESR.
[0095] The liquid working electrolyte of the capacitor 100 has a high oxidizing ability towards the anode metal and is therefore able to penetrate the polymer film and oxide layer 2 and repair oxide defects.
[0096] The conductivity of the polymer layer 4 cannot be measured directly. However, film resistance is the inverse of conductivity. Film resistance is the electrical resistance of a layer of polymer of a particular thickness at a defined distance. Film resistance can be measured experimentally by applying a current through temporary electrodes to the polymer test film 200.
[0097] 3 shows an illustrative test film 200. A 11.5 cm by 21.5 cm MYLAR foil 201 was cut and mounted in a sample holder. 2 ml of viscous polymer sample was applied onto the foil. The polymer sample was smoothly dispersed with a hand coater to form a polymer film 202.
[0098] The polymer film 202 was then dried in an oven at 180° C. for 60 minutes. Several silver electrodes 203 were applied onto the polymer film 202 and dried in an oven at 130° C. for 20 minutes. The electrodes 203 should be at least 2 cm in length and have a distance of 2 cm from each other.
[0099] As shown in FIG. 1, a separator layer 5 is deposited on the surface of the polymer layer 4 opposite the oxide layer 2 and the anode foil 1 .
[0100] A separator layer 5 is sandwiched between the anode and cathode to avoid direct contact between the electrodes.
[0101] The breakdown phenomenon of the capacitor 100 also depends on the separator characteristics such as the type of material, density and thickness. The aforementioned characteristics are determined more specifically by the separator resistivity, which determines the breakdown voltage. The separator is impregnated with a liquid electrolyte to fill all the pores in the separator that the polymer nanoparticles could not reach during impregnation. In this way, the capacitance of the capacitor 100 can be maximized.
[0102] The separator layer 5 comprises natural and / or artificial fibrous materials arranged in a single layer or multiple layers and has an average mass / area ratio of 8.0 g / m 2It should be higher.
[0103] The separator includes a filter membrane layer in this embodiment, and the filter membrane material may include PET, nylon, PTFE (polytetrafluoroethylene) and / or PES (polyethersulfone). The filter membrane includes pores with a pore size greater than 0.22 μm. In a further embodiment, the separator may include an additional support layer that supports the porous, fragile membrane.
[0104] The separator has a minimum thickness of 50 μm and a weight of 0.30 g / cm to allow for application of voltages higher than 200 V. 3 The resulting resistivity should be higher than 5%, preferably higher than 15%.
[0105] On the side of the separator layer 5 opposite the polymer layer 4 is disposed a metal cathode foil 6 comprising a cathode layer 6 to form the cathode of the capacitor 100. The surface of the cathode foil 6 is roughened to a spongy or grape-like structure and the outer surface may be stabilized by a chemical phosphating treatment and / or by a thermal or electrochemical oxidation treatment.
[0106] The liquid electrolyte is impregnated on the surface of the separator and the anode and cathode. The liquid electrolyte has the ability to oxidize the anode metal, especially aluminum. The electrical conductivity of the liquid electrolyte at 30° C. should be at least 200 μS / cm. The water content of the electrolyte should be 0.5% to 5%, preferably 0.5% to 3% (weight percent).
[0107] The electrolyte is capable of improving the oxide layer 2 so that it can withstand voltages of more than 150V, preferably more than 250V, more preferably up to at least 400V.
[0108] During the life of the capacitor 100, defects may occur on the surface of the oxide layer 2. Therefore, a low-conductivity electrolyte is used to repair the defects on the surface of the oxide layer 2 by oxidation of the anode metal. A high oxidation ability of the electrolyte is related to a high sparkover voltage.
[0109] In addition, the effective oxidation capacity is improved by optimizing the water content of the electrolyte, which is a liquid electrolyte.
[0110] The liquid electrolyte has the added advantage of filling the pores in all layers, thus maximizing capacitance which may be reduced by imperfect contact between the polymer layer 4 and the hydrated or non-hydrated oxide layers 2 and 3. Such imperfect contact may result in capacitance degradation over the life of the capacitor.
[0111] The breakdown voltage across the capacitor 100 is strongly dependent on the total conductivity between the anode foil 1 and the cathode foil 6 .
[0112] Furthermore, the breakdown voltage also depends on the quality of the oxide layer 2 applied on the anode foil 1. In particular, the surface stability of the oxide layer 2 plays an important role. The quality of the oxide layer 2 is influenced by the content of phosphorus inclusions, which stabilizes the oxide layer 2 against hydration and sparking phenomena during the life of the capacitor 100.
[0113] In another embodiment shown in FIG. 4, a capacitor 100 is fabricated with an additional viscous electrolyte layer 7 between the separator 5 and the polymer layer 4 to increase the breakdown voltage.
[0114] In a further embodiment shown in FIGS. 5 and 6, a further layer is arranged between the cathode foil 6 and the separator layer 5 .
[0115] In FIG. 5, a carbon layer 8 is applied to the surface of the cathode foil 6 .
[0116] In Figure 6, a titanium layer 9 or alternatively a titanium oxide layer 2 and a silicon dioxide layer 10 are arranged between the cathode foil 6 and the separator layer 5. These layers 9 and 10 can further increase the breakdown voltage.
[0117] Reference sign 1 anode foil / layer 2. Oxide layer 2a Amorphous oxide layer 2b Crystalline oxide layer 3. Hydrated oxide layer 4 Polymer Layer 5 Separator layer 6 Cathode foil 7 Electrolyte layer 8 Carbon Layer 9 Titanium layer 10 Silicon dioxide layer 100 Capacitor 200 Test Film 201 MYLAR foil 202 Polymer Film 203 Test Electrode
Claims
1. 1. A hybrid polymer capacitor comprising several layers between an anode layer and a cathode layer, the hybrid polymer capacitor comprising a non-hydrated metal oxide layer having a thickness of at least 100 nm in a stacking direction, a hydrated metal oxide layer disposed on a surface of the non-hydrated metal oxide layer, and a liquid electrolyte having a conductivity of at least 200 μS / cm at 30° C. and a water content of at least 0.5%, the hydrated metal oxide layer and the non-hydrated metal oxide layer being impregnated with the liquid electrolyte.
2. The hybrid polymer capacitor of claim 1 , wherein the non-hydrated metal oxide layer is applied directly to a surface of the anode layer.
3. The hybrid polymer capacitor of claim 1 or 2, wherein the hydrated metal oxide layer has a thickness of at least 10 nm in the stacking direction.
4. 4. The hybrid polymer capacitor according to claim 1, wherein the metal oxide is aluminum oxide, in particular alumina.
5. The hybrid polymer capacitor of claim 1 , wherein the metal oxide layer is doped with phosphate anions.
6. The hybrid polymer capacitor of claim 1 , wherein the non-hydrated metal oxide layer comprises a stack of an amorphous metal oxide layer and a crystalline metal oxide layer.
7. 7. The hybrid polymer capacitor of claim 1, wherein the nominal voltage of the capacitor is greater than 150V, preferably greater than 250V.
8. 4. The hybrid polymer capacitor of claim 1 , wherein a polymer layer comprising a conductive polymer is disposed between one or more of the metal oxide layers on one side thereof and the cathode layer on the opposite side thereof.
9. The hybrid polymer capacitor of claim 8 , wherein the polymer layer comprises a PEDOT:PSS polymer material.
10. 10. The hybrid polymer capacitor of claim 8 or 9, wherein a separator layer comprised of a separator resistivity of at least 5% is disposed between the polymer layer and the cathode layer.
11. 11. The hybrid polymer capacitor of claim 10, wherein the separator resistivity is at least 15%.
12. 12. The hybrid polymer capacitor of claim 10 or 11, wherein the separator layer has a minimum thickness of 50 μm.
13. The density of the separator layer is at least 0.30 g / cm 3 13. The hybrid polymer capacitor of claim 10, wherein
14. The average mass / area ratio of the separator layer is 8.0 g / m 2 The hybrid polymer capacitor of claim 10 , wherein the hybrid polymer capacitor is greater than or equal to 100 μm.
15. 15. The hybrid polymer capacitor of claim 10, wherein an intermediate electrolyte layer is disposed between the polymer layer and the separator layer.
16. 16. The hybrid polymer capacitor of claim 10, wherein one or more of a carbon layer, a titanium layer, a titanium oxide layer, and a silicon dioxide layer are disposed between the cathode layer and the separator layer.
17. 17. The hybrid polymer capacitor of claim 1, wherein the layers between the anode layer and the cathode layer are stacked in the stated order.
18. 18. The hybrid polymer capacitor of claim 1, which is a flat-type or wound-type capacitor.
Citation Information
Patent Citations
Electrolytic capacitor
JP1986101017A
Method for manufacturing electrolytic capacitor and electrolytic capacitor
JP2009111174A
Method for manufacturing electrolytic capacitors with high nominal voltage
JP2009508342A
Manufacturing method for winding type solid electrolytic capacitor
JP2013214674A
Solid electrolytic capacitors
JP2013524480A